2000
DOI: 10.1164/ajrccm.162.3.9908018
|View full text |Cite
|
Sign up to set email alerts
|

Infections with Mycobacterium tuberculosis and Mycobacterium avium among HIV-infected Patients after the Introduction of Highly Active Antiretroviral Therapy

Abstract: The impact of highly active antiretroviral therapy (HAART) among human immunodeficiency virus (HIV)-infected patients on the incidences of mycobacterial infections has not been studied in detail. We assessed incidences of mycobacterial diseases among HIV- infected patients following the introduction of HAART, using data from the EuroSIDA study, a European, multicenter observational cohort of more than 7,000 patients. Overall incidences of Mycobacterium tuberculosis (TB) and Mycobacterium avium complex (MAC) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
3
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(67 citation statements)
references
References 27 publications
5
58
3
1
Order By: Relevance
“…The incidence rate ratio for TB among people on and off ART, IRR TB ART , has been measured in several studies (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), giving an average value of 0.39 but ranging from 0.2 to 0.75 (SI Appendix, section 4). We assume that the duration of TB disease bears the same relationship to the incidence as it does for people not on ART (SI Appendix, section 4).…”
Section: Methodsmentioning
confidence: 99%
“…The incidence rate ratio for TB among people on and off ART, IRR TB ART , has been measured in several studies (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), giving an average value of 0.39 but ranging from 0.2 to 0.75 (SI Appendix, section 4). We assume that the duration of TB disease bears the same relationship to the incidence as it does for people not on ART (SI Appendix, section 4).…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, in the USA and Western Europe, a decline in the incidence of TB in HIV-infected patients has been observed in the last decades; however, remarkable regional differences have been found in Europe, with rates four to seven times higher in southwest Europe than in other European regions [96,97].…”
Section: Tb and Other Mycobacteriosismentioning
confidence: 99%
“…The nature and prevalence of lung complications was characterized by the Pulmonary Complications of HIV Infection Study (40) more than 15 years ago, before ART increased life expectancy. Although studies in the combination ART era have reported changes in pulmonary complications (29,30,41,42), HIV-related lung complications have not been systematically reassessed in multisite cohorts or compared among international sites with wide variations in ART use.…”
Section: Spectrum Of Hiv-associated Lung Infections and Complicationsmentioning
confidence: 99%